pH-RESPONSIVE EUDRAGIT® S-100 COATED CHITOSAN NANOPARTICLES FOR TARGETED CURCUMIN DELIVERY IN ULCERATIVE COLITIS: FORMULATION AND OPTIMIZATION - SAHU, NEELESH KUMAR; LARIYA, NARENDRA KUMAR (International Journal of Applied Pharmaceutics, 2025)
Objective: This study aimed to develop and optimize pH-responsive Eudragit S-100 coated chitosan Nanoparticles (NPs) for targeted curcumin delivery in Ulcerative Colitis (UC). The objectives included enhancing curcumin's bioavailability, achieving colon-specific release through mucoadhesive, pH-sensitive nanocarriers, and evaluating their long-term stability. Methods: Curcumin-loaded chitosan NPs were prepared via ionotropic gelation using Sodium Tripolyphosphate (STPP) and coated with Eudragit S-100 via solvent evaporation. Nine formulations (F1–F9) were optimized by varying chitosan (250–750 mg) and STPP (0.50–1.00% w/v) concentrations. The NPs were characterized for particle size, zeta potential, Entrapment Efficiency (EE), morphology (SEM), and in vitro drug release in simulated gastrointestinal pH (1.2 → 7.5). Release kinetics were analyzed using Zero-Order, Higuchi, and Korsmeyer-Peppas models. Stability studies were conducted at 4 °C, 28 °C/65% RH, and 40 °C/75% RH for 90 days to assess particle size and drug retention. Results: The optimized formulation (F4: 500 mg chitosan, 0.50% w/v STPP) exhibited a mean particle size of 355.5 nm, high EE (76.65%), and a zeta potential of −36.32 mV, confirming colloidal stability. Coated NPs demonstrated pH-dependent release: minimal in acidic pH (2.32% at pH 1.2) and sustained in colonic pH (98.33% at pH 7.5). Release kinetics followed the Korsmeyer-Peppas model (R² = 0.9892, n = 0.62), indicating anomalous transport. Stability studies revealed excellent retention of particle size (≤361.4 nm) and drug content (>99%) under varied storage conditions, confirming long-term stability. Conclusion: Eudragit S-100 coated chitosan NPs successfully addressed curcumin's solubility and bioavailability challenges while ensuring pH-responsive, targeted colonic delivery. The optimized formulation (F4) exhibited robust stability, making it a promising candidate for UC therapy. Future studies should focus on in vivo efficacy and clinical translation.